Simulated Translation Bureaus: Experiential Learning and Internationalization in Translation Education - Kerremans, Koen; Egdom, Gy-Walt van; Fernandez-Parra, Maria; Salmi, Leena; Bindels, Jaap. (Netherlands, 2026)
Simulated translation bureaus offer an innovative and holistic approach within translation education. Students set up a fictitious translation bureau and perform authentic translation tasks under realistic conditions but within a safe educational environment. This article takes a closer look at setting up and implementing simulated translation bureaus, highlighting their educational value and the significant benefits students can gain from this didactic concept. Working in a simulated professional environment allows students to develop essential skills, including subject-specific, technological, and interpersonal competences. Moreover, this method promotes the internationalization of translation education, enhancing students’ intercultural competence. The holistic nature of simulated translation bureaus ensures that students are not only proficient in translation, but also equipped with the necessary soft skills needed in a multicultural work environment. This approach is in line with current educational trends and the demands of the professional translation industry.
Keywords:
simulated translation bureaus, skills labs, translation education, experiential learning, competence acquisition, internationalization, intercultural competence